Profile of Mathematical Beliefs of State Junior High School 1 Palu Students in Solving Two-Variable Linear Equations: Viewed from Gender - Zahratunnisa Zahratunnisa; Pathuddin Pathuddin; Fajriani Fajriani; Mubarik Mubarik (Journal of Educational Sciences, 2026)
This study describes the profile of mathematical beliefs of students at State Junior High School 1 Palu in solving two variable linear equations, viewed from masculine and feminine gender tendencies. A qualitative descriptive approach was employed, involving two Grade VIII students identified through the Bem Sex Role Inventory (BSRI) questionnaire as masculine (SM) and feminine (SF). Data were collected using written tests and semi-structured interviews based on Bandura’s self-efficacy framework, covering magnitude, strength, and generality dimensions. The findings show that SM demonstrated strong and positive mathematical beliefs, characterized by confidence in solving complex problems, persistence despite difficulties, and the ability to generalize prior knowledge to new contexts. In contrast, SF exhibited moderately positive beliefs, marked by optimism and commitment but requiring reinforcement in consistency, resilience, and procedural accuracy. These results highlight differences in mathematical beliefs based on gender tendencies and emphasize the importance of considering gender perspectives in mathematics learning. The study provides implications for teaching strategies that strengthen students’ confidence and problem-solving abilities.